Perlindungan Hukum Terhadap Investor Publik Melalui Pembelian Kembali Saham (Buy Back) Dalam Keadaan Pasar Yang Berpotensi Krisis Menurut Peraturan Otoritas Jasa Keuangan Nomor 3/SEOJK.04/2020 - Putri Habibah Siregar (Iuris Studia: Jurnal Kajian Hukum, 2022)
The results of this study indicate that the buyback arrangement based on the Company Law is too general and minimalistic so that it requires special regulations as implementing regulations, namely Rule Number XI.B.2 which is intended for the implementation of buybacks during normal market conditions, while during crisis market conditions, regulations The applicable regulations are POJK Number 3/POJK.04/2020, the validity of this OJK Regulation is temporary, only when the market situation tends to fluctuate significantly. Regarding the concept of legal protection for investors, it is not sufficiently regulated in the POJK because it has been comprehensively regulated in OJK Regulation Number: 1/POJK.07/2013 concerning Consumer Protection in the Financial Services Sector. Thus, the form of protection regulated in the POJK is solely for issuers/public companies